Selection of Investment Projects by Monte Carlo Method in Risk Condition - Sinytskyi, M. E.; Motsnyi, F. V. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
The Monte Carlo method (also known as the Monte Carlo simulation) was proposed by Nicholas Metropolis, S. Ulam and Jhon Von Neiman in 40-50-th years of the past century. The method can be widely applied to analysis of investment projects due to the advantages recognized both by practitioners and the academic community. The balance model of a project with discountedfinancialflows has been studied. The Monte Carlo model for project with low and high correlated net present value (NPV) parameters has been implemented for Microsoft Excel and Google Docs spread-sheet solution. A distinct graduation of risk was identified. A necessity of account of correlation effects and the use of multivariate imitation during the project selection has been demonstrated.